Hubungan Dukungan Keluarga Dan Motivasi Diri Dengan Kepatuhan Minum Obat Pada Pasien Penyakit Jantung Koroner - Praptiningtiyas, Ariska; Sunanto, Sunanto; Kusyairi, Achmad (NHM PRESS, 2023)
Coronary heart disease is caused disorders of the heart, blood vessels and narrowing arteries, the presence spots that accumulate in blood vessels.Coronary heart function as nutrition and O2 for heart muscle cells. Family support can be used very important coping strategy overcome problems that occur.This study aims determine the relationship between family support and self motivation with adherence taking medication coronary heart patients Poli RSUD dr. Haryoto Lumajang The design in cross sectional approach. The sampling accidental sampling where the population of the respondent was taken sample based on sample that happened to be found. The questionnaire used was Sociodemographic,Family Support, and Motivation with 66 respondents. The results of study obtained data low family support of 28 people (42.4%), low motivation of 39 people (59.1), and non-adherence to treatment of 38 people (57.6%). The correlative test there a relationship between factors Family Support and Motivation with Medication Adherence with p value of 0.000 <0.05, which means Ha accepted where there a relationship between family support and motivation with medication adherence in coronary heart patients. Family support will affect person taking treatment because external support make a person feel cared for, needed take treatment, apart from family support, self-motivation factor a person take treatment .